2017
DOI: 10.1038/s41598-017-07696-6
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to prolonged hypoxia alters hemoglobin isoform expression and increases hemoglobin oxygen affinity and aerobic performance in a marine fish

Abstract: Hemoglobin (Hb) multiplicity is common in fish, yet despite its ubiquitous nature, the functional significance is unclear. Here we explore the hypothesis that Hb multiplicity plays a role in hypoxia tolerance using the red drum (Sciaenops ocellatus). Red drum is an economically and ecologically important species native to coastal regions and estuaries of the Gulf of Mexico – habitats that routinely experience pronounced hypoxic events. Using a transcriptomic approach, we demonstrate that red drum red blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 53 publications
(50 reference statements)
1
23
0
Order By: Relevance
“…Blue crab ( Callinectes sapidus ) and various other crustacean species have been shown to be tolerant of low oxygen conditions as they are capable of regulating oxygen transport 37 presumably due to induction of oxygen-transporting proteins. Fish have been shown to increase hemoglobin levels in response to low oxygen conditions 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Blue crab ( Callinectes sapidus ) and various other crustacean species have been shown to be tolerant of low oxygen conditions as they are capable of regulating oxygen transport 37 presumably due to induction of oxygen-transporting proteins. Fish have been shown to increase hemoglobin levels in response to low oxygen conditions 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A follow‐up review of hypoxia tolerance in various species of intertidal sculpins, revealed p crit values ranging 26–36 mmHg (Richards, ). p crit in the marine red drum, Sciaenops ocellatus (L. 1766) is 28–36 mmHg at 24°C (Pan et al, ). p crit Has been examined in the context of a fast‐slow lifestyle continuum in fishes, with values ranging from 19–38 mmHg (Stoffels, ).…”
Section: Discussionmentioning
confidence: 99%
“…6A and B, at its NOEC (0.8 µg/L), AEO-7 did not affect the level of hemoglobin in our zebra sh embryos, whereas at a concentration of 3.2 μg/L, the number of hemoglobin-positive cells was reduced. This reduction could re ect decreased production of red blood cells in the bone marrow and/or lowered hemoglobin synthesis in erythrocytes due to blockage of heme synthesis [66,67].…”
Section: At Its Noec Aeo-7 Does Not Cause Hematopoietic Toxicity In mentioning
confidence: 99%